Produção e Qualidade Física dos Frutos do Abacaxi sob Diferentes Lâminas e Frequências de Irrigação - Souza, Olegário Pinheiro de; Zanini, José Renato [UNESP]; Torres, Jose Luiz Rodrigues; Barreto, Antonio Carlos; Souza, Eduardo Luís Campos [UNESP] (My University, 2012)
The objective of this study was to evaluate the performance of pineapple cultivar Smooth Cayenne as the physical production and the quality of the fruit when subjected to different frequencies of water dpeth and soil water in Triângulo Mineiro - Uberaba-MG. The experimental area soil is Oxisol, clay loam sandy and soft undulating local relief. A randomized block design in a factorial 4 x 2 with four levels of soil water depth (50%, 75%, 100% and 125%) of crop evapotranspiration (ETc) and two irrigation frequencies (1 day and 3 days = F1 = F2) and four replications was utilized. The crop productivity, number of seedlings, mean weight, diameter, and hardness of the fruit, plus water use efficiency were evaluated. Productivity was not significantly affected by the water depth and by the frequency of water applied; however the fruit shell resistance, the efficiency of water use, and ratoon seedlings were significantly influenced by irrigation, the water depth of 50% of the crop evapotranspiration (ETC) provided greater efficiency of water use for the production of pineapple fruit.

O objetivo deste estudo foi avaliar o desempenho do abacaxizeiro cultivar Smooth cayenne quanto à produção e qualidade física dos frutos, quando submetido a diferentes laminas e frequências de reposição de água no solo, na região do Triângulo Mineiro, em Uberaba-MG. O solo da área experimental é um Latossolo Vermelho distrófico, textura franco-argilo-arenosa e relevo local suave ondulado. Utilizou-se delineamento em blocos casualizados, num esquema fatorial 4 x 2, com quatro lâminas de reposição de água no solo (50%, 75%, 100% e 125%) da evapotranspiração da cultura (ETc) e duas frequências de irrigação (1 e 3 dias), com quatro repetições. Avaliou-se a produtividade da cultura, número de mudas, peso médio e diâmetro médio dos frutos, resistência do fruto e eficiência do uso da água. A produtividade não foi afetada significativamente pelas lâminas e freqüência de água aplicada; a resistência do fruto com casca, eficiência do uso da água e mudas tipo rebentão foram significativamente influenciados pelas lâminas de irrigação; a lâmina de reposição de 50% da evapotranspiração da cultura (ETc) proporcionou maior eficiência do uso da água para produção de abacaxi.
Pineapple production and physical quality under different irrigation frequencies and water depths
Keywords: Ananas comosus; Evapotranspiration; Irrigation management; Precipitation; crop production; cultivar; evapotranspiration; fruit production; irrigation; Oxisol; precipitation (climatology); soil water; water depth; water use efficiency; Brazil; Minas Gerais; Triangulo Mineiro